PEMBANGUNAN COMPILER DOMAIN SPECIFIC LANGUAGE SEBAGAI GENERATOR FORM HTML MENGGUNAKAN PYTHON SLY - Adiyoso, Wibisono; Susetyo, Yeremia Alfa (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
The rapid development of information technology has a significant impact on the way companies operate. Companies can utilize technology to simplify and accelerate their business processes, including recording and managing transactional data. PT XYZ is one of the largest retail companies, with a vast amount of data and requiring various types of different HTML forms. Therefore, standardization in program code writing is necessary to minimize errors and facilitate application maintenance. This research aims to build a Compiler Domain Specific Language (DSL) as a web-based HTML form generator for PT XYZ. The study uses the Python SLY library, passing the Lexer and Parser processes in DSL development. The result of this research is a web-based HTML form generator that facilitates developers in creating standardized and automatic HTML forms. The use of DSL can speed up the program code writing process, minimize errors, and create structured and easily understood code by developers.